PROPOSED EMPLOYEE INFLUENCER PROGRAM TO STRENGTHEN EMOTIONAL ENGAGEMENT IN GOVERNMENT COMMUNICATION A CASE STUDY OF WEST JAVA PROVINCIAL GOVERNMENT - Cindy Intan Audya Putri; N. Nurlaela Arief (RADJA PUBLIKA, 2025)
This study proposes an employee influencer program aimed at strengthening emotional engagement within government communication, focusing on the West Java Provincial Government as a case study. Recognizing the critical role of emotional connection in enhancing employee motivation, trust, and organizational culture, this research explores how employee influencers can serve as authentic communicators to foster deeper engagement both internally and externally. Employing a qualitative research design with a library research method, the study systematically reviews existing literature, government communication policies, and case studies on employee advocacy and influencer strategies in public sector organizations. Through content analysis, key themes such as trust-building, authentic communication, leadership support, and social media governance are examined to understand the factors that contribute to successful employee influencer programs. The findings suggest that well-structured influencer initiatives, supported by clear guidelines and continuous training, can significantly improve emotional engagement, enhance transparency, and build stronger relationships between government employees and stakeholders. The study highlights the importance of aligning influencer activities with organizational values and communication objectives to maximize impact. This research contributes to the growing body of knowledge on internal communication strategies in government institutions and offers practical recommendations for designing and implementing employee influencer programs to achieve sustainable emotional engagement. Future research is encouraged to empirically validate these findings through field studies and stakeholder feedback.